Religious and Social Conceptions of Divorce: A Case Study of Cibogo Community in Cirebon - Shabrina Riana; Rizky Hadi Purnama; Tasya Diana Amalia; Himawan; Nurlaili Khikmawati; Rizkia Fatur Rochma (UIN Siber Syekh Nurjati Cirebon, 2024)
Marriage is seen as a social institution that legally binds two individuals, while divorce marks the legal and social end of that relationship. The complexity of marriage involves cultural, religious, and social factors, and family issues often lead to divorce. The aim of this study is to identify the causes and impacts of divorce. Using a case study approach and qualitative research methods, the study employs conflict theory as its theoretical framework. Conflict theory emphasizes how social, economic, and political factors influence marital dynamics, ultimately contributing to the likelihood of divorce. Marital conflicts can arise from an unequal division of household labor, differences in opinion, or infidelity, often triggered by emotional tension or unmet needs. External factors, such as financial difficulties, unemployment, or cultural differences, can further strain the relationship. Divorce is often seen as a response to perceived injustice within the marriage. If one partner feels exploited or if there is an imbalance of power, divorce may become a means of seeking justice. Conflict theory provides insights into how these social, economic, and political factors shape marital relationships, helping individuals understand the underlying causes of marital conflicts and the potential for divorce.